Analysis of Collaborative Governance in the Development of Creative Economy Sector in Kepulauan Anambas Regency - Janah, Samrotul; Puspita Dewi, Maya (Jurnal Sains Sosio Humaniora, 2026)
This study aims to analyze collaborative governance in the development of the creative economy sector in Kepulauan Anambas Regency. The research uses the collaborative governance model of Ansell and Gash (2008) which focuses on initial conditions, institutional design, facilitative leadership, collaborative processes, and interim outcomes. The research method used is a descriptive qualitative approach through in-depth interviews, observations, and documentation with informants from local governments, creative business actors, cooperatives, communities/non-governmental organizations, and private companies. The results of the study show that collaborative governance in the development of the creative economy begins to take shape through the involvement of various stakeholders across sectors. However, the collaboration process has not run optimally due to limited infrastructure, human resources, and budget. The institutional design aspect is still weak because there are no regulations and forums that support collaboration. Facilitative leadership and collaborative processes are still dominated by informal relationships and individual initiative of actors. Nevertheless, the collaboration has produced an initial positive impact in the form of increasing the number of business legalities, strengthening the capacity of business actors, expanding the promotion of local products, and growing the community's economy. This research implies the importance of institutional strengthening, the establishment of structured and formal collaboration mechanisms, and increasing stakeholder participation to realize the development of a sustainable and inclusive creative economy, especially in Kepulauan Anambas Regency.